Symbolism of a detail. Architectural masterpieces of the UNESCO Heritage Town of Zamość - Kielin, Katarzyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The Town of Zamość is located in the south-eastern part of Poland and is the worldwide UNESCO Heritage fortress whose beginning dates back to the end of the 16th century. Built in cruda radice, the Zamość architectural value derives primarily from its unique, historical plan which remained the original compositional form envisioned by a brilliant, broad-minded, ambitious man of European Renaissance – Jan Zamoyski. Urban layout of the Town mimics the anthropomorphic distribution of key body parts encapsuled within the frame of the most up-to-date examples of ‘architectura militaris’ for those times. The smart spatial organization of space allowed not only for the flexible introduction of new functions in larger, urban scale but also the exposition of the intricate beauty of architectural ornamentation and detail of crucial representative buildings. Within the plethora of reverberating, classic examples of details there are also some which convey important, symbolic meaning which is very much connected to the history of the Town.